Ang liwanag sa dagat - De Jesus, Jenny P. (Science supplementary materials for the k to 12 curriculum, 2014)
"There are many wonders under the sea. One of them is the magnificent glow of bioluminescent creatures. These are animals that have the ability to emit or give off light. The story features some bioluminescent sea creatures. It focuses on how these animals produce and emit light. The children will be fascinated to know how bioluminescence is used."--Preface.